Sustainable Design Optimization in Fast-track Projects: A Case Study of Hospitality in Bali - Widanan, I Wayan; Adhika, I Made; Dwijendra, Ngakan Ketut Acwin; Yudantini, Ni Made (ASTONJADRO, 2025)
The hospitality industry in Bali faces a significant challenge in adopting green architectural practices amid the increasing demand for fast development through fast-track methods. Although this method accelerates the completion of projects, many criticize its impact on environmental sustainability. This article explores sustainable design optimization strategies in fast-track projects by highlighting elements such as utilizing local materials, energy efficiency, and natural resource management. Case studies on several eco-friendly hotels in Bali were used to develop recommendations for architects and developers to implement design models that accelerate construction without neglecting sustainability. This research uses a qualitative approach with case study methods and in-depth interviews with industry experts. The study results show that applying environmentally friendly technology and structured project management can improve sustainability in fast-track projects. Therefore, the integration of green design practices into fast construction methods is an essential solution to support the environmental sustainability and hospitality industry in Bali.